No Relationships Between the Within-Subjects’ Variability of Pain Intensity Reports and Variability of Other Bodily Sensations Reports - Agostinho, Mariana; Canaipa, Rita; Honigman, Liat; Treister, Roi (Frontiers in Neuroscience, 2019)
Purpose: The subjective nature of pain assessment and its large variance negatively affect patient-health care provider communication, and reduce the assay sensitivity of pain clinical trials. Given the lack of an objective gold standard measure, identifying the source (true or error) of the within-subject variability of pain reports is a challenge. By assessing the within-subjects variability of pain and tastes reports, alongside with interoceptive measures, , the current study is aimed to investigate if the ability to reliably report bodily sensations is a cross modal characteristic. Patients and methods: This prospective study enrolled healthy volunteers from local universities. After consenting, subjects underwent the Focus Analgesia Selection Task (FAST), to assess within-subjects variability of pain reports in response to experimental noxious stimuli; a taste task, that similarly assess within subjects variability of tastes (salty and sweet) intensity reports, and (3) the heartbeat perception task, an interoceptive task aimed to assess how accurate subjects are in monitoring and reporting their own heartbeat. In addition, all subjects completed the Multidimensional Assessment of Interoceptive Awareness (MAIA), the Perceived Stress Scale (PSS) and Hospital Anxiety and Depression Scale (HADS). Spearman’s correlations were used to assess relations between all measures. Results: Sixty healthy volunteers were recruited. Variability of intensity reports of different modalities were independent of each other (P>0.05 for all correlations). The only correlation found was within modality, between variability of intensity reports of salt and sweet tastes (Spearman’s r=.477, P<.001). No correlations were found between any of the tasks results and questionnaire results. Conclusion: within-subjects variability of pain reports do not relate to variability of reports of other modalities, or to interoceptive awareness. Further research is ongoing to investigate the clinical relevance of within-subjects’ variability of pain reports.